2004
DOI: 10.1038/sj.onc.1207971
|View full text |Cite
|
Sign up to set email alerts
|

Multidomain Bcl-2 homolog Bax but not Bak mediates synergistic induction of apoptosis by TRAIL and 5-FU through the mitochondrial apoptosis pathway

Abstract: The death ligand TRAIL synergizes with DNA-damaging therapies such as chemotherapeutic drugs or ionizing irradiation. Here, we show that the synergism of TRAIL and 5-fluorouracil (5-FU) and cross-sensitization between TRAIL and 5-FU for induction of apoptosis, entirely depend on Bax proficiency in human DU145 and HCT116 carcinoma cells. DU145 prostate carcinoma cells that have lost Bax protein expression due to mutation fail to release cytochrome c and to activate caspase-3 and -9 when exposed to TRAIL and 5-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 50 publications
(52 reference statements)
7
84
1
2
Order By: Relevance
“…The critical role of both Bak and Bax during apoptosis induction by p14 ARF is further underlined by the observation that their combined loss completely impaired mitochondrial activation, as evidenced by the failure of Bax/Bak double-deficient cells to release cytochrome c upon p14 ARF expression. This is in clear contrast to other proapoptotic stimuli, that is, death receptor ligands such as TRAIL (von Haefen et al, 2004;Wendt et al, 2005) or the BH3-only proteins Nbk (Gillissen et al, 2003) or Puma (Yu et al, 2003) that completely rely on the presence of Bax, but not Bak, to facilitate the activation of mitochondria and subsequent execution of apoptotic cell death in human cancer cells. Consequently, we observed that epirubicininduced apoptosis occurred in a predominantly Baxdependent manner in our systems.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The critical role of both Bak and Bax during apoptosis induction by p14 ARF is further underlined by the observation that their combined loss completely impaired mitochondrial activation, as evidenced by the failure of Bax/Bak double-deficient cells to release cytochrome c upon p14 ARF expression. This is in clear contrast to other proapoptotic stimuli, that is, death receptor ligands such as TRAIL (von Haefen et al, 2004;Wendt et al, 2005) or the BH3-only proteins Nbk (Gillissen et al, 2003) or Puma (Yu et al, 2003) that completely rely on the presence of Bax, but not Bak, to facilitate the activation of mitochondria and subsequent execution of apoptotic cell death in human cancer cells. Consequently, we observed that epirubicininduced apoptosis occurred in a predominantly Baxdependent manner in our systems.…”
Section: Discussionmentioning
confidence: 96%
“…Proapoptotic Bak is controlled preferentially by Bcl-x L and Mcl-1 until released by proapoptotic signals, that is, by Noxa (Mcl-1) and Bad (Bcl-x L ) (Willis et al, 2005). These proteins appear to play selective roles, which may delineate a higher degree of specificity to the regulation of Bax and Bak in p14 ARF -induced cell death in analogy to other apoptosis-promoting stimuli (Theodorakis et al, 2002;Gillissen et al, 2003;Yu et al, 2003;von Haefen et al, 2004;Wendt et al, 2005), which clearly demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in HCT116 and other cell line models have indicated that Bak cannot compensate for loss of Bax to induce apoptosis in response to TRAIL (LeBlanc et al, 2002;Theodorakis et al, 2002;Han et al, 2004;von Haefen et al, 2004). HCT116 Bax-null cells express similar levels of Bak as the parental cells (Figure 1a), and Bak has been shown to be functional in HCT116 Bax-null cells (Theodorakis et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…First, we determined the DC m dissipation by means of the DC m -sensitive fluorochrome 3,3 dihexyloxacarbocyanine iodide (DiOC 6 (3)) ( Figures 2a and b). Second, we assessed the relocation of a Bax-GFP fusion protein (von Haefen et al, 2004) from Thapsigargin restores immunogenic cancer cell death I Martins et al a diffuse to a punctate (presumably mitochondrial) pattern (Figures 2c and d). Thus, both CDDP and OXP induced similar mitochondrial perturbations (Figure 2).…”
Section: Thapsigargin Restores Immunogenic Cancer Cell Death I Martinmentioning
confidence: 99%